2021
DOI: 10.3390/w13111461
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Genetic Elements Drive the Antibiotic Resistome Alteration in Freshwater Shrimp Aquaculture

Abstract: Shrimp aquaculture environments are a natural reservoir of multiple antibiotic resistance genes (ARGs) due to the overuse of antibiotics. Nowadays, the prevalence of these kinds of emerging contaminants in shrimp aquaculture environments is still unclear. In this study, high-throughput sequencing techniques were used to analyze the distribution of ARGs and mobile genetic elements (MGEs), bacterial communities, and their correlations in water and sediment samples in two types of typical shrimp (Procambarus clar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 70 publications
1
1
0
Order By: Relevance
“…In particular, intI1 demonstrated a positive correlation with over 10 generals; however, among those, Flavihumibacter (p < 0.05) and Hydrogenophaga (p < 0.05) were the only genera that showed significant and positive associations. This is also in accordance with earlier observations, which showed that Hydrogenophaga plays an important role in the spread and variation of ARGs and intI1 in freshwater environments [54]. For the tetA, 10 of the 30 genera were positively correlated, but only Acinetobacter was significantly and positively correlated (p < 0.01), which has been earlier identified as a host for ARGs in aquaculture ponds [55].…”
Section: Interrelationship Among Microbial Community Inti1 and Argssupporting
confidence: 92%
“…In particular, intI1 demonstrated a positive correlation with over 10 generals; however, among those, Flavihumibacter (p < 0.05) and Hydrogenophaga (p < 0.05) were the only genera that showed significant and positive associations. This is also in accordance with earlier observations, which showed that Hydrogenophaga plays an important role in the spread and variation of ARGs and intI1 in freshwater environments [54]. For the tetA, 10 of the 30 genera were positively correlated, but only Acinetobacter was significantly and positively correlated (p < 0.01), which has been earlier identified as a host for ARGs in aquaculture ponds [55].…”
Section: Interrelationship Among Microbial Community Inti1 and Argssupporting
confidence: 92%
“…Sequencing of 41 plasmid-transmitted ARGs showed the presence of a wide range of ABs, including aminoglycosides, OXA-type ß-lactams, chloramphenicol, fluoroquinolone, macrolides, rifampicin, tetracycline, trimethoprim and sulfonamide. The association of ARGs with mobile genetic elements that enable their dissemination has been demonstrated worldwide (Gillings et al, 2008; Gao et al, 2012; Fang et al, 2021). Previous studies in the Mekong Delta have shown, for example, that sul 2 genes have been detected in association with integrons and plasmids (Pham et al, 2018).…”
Section: Introductionmentioning
confidence: 99%